The Effect of Personalized Marketing on Consumer Retention through Consumer Satisfaction and Consumer Trust - Indar Riyanto; Didit Haryadi; Fuadi Fuadi; Saeful Fachri (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Consumer retention is shaped by personalized marketing, built on consumer trust and satisfaction. This study aims to identify the effect of personalized marketing on consumer retention, focusing on consumer satisfaction and trust in the e-commerce sector. The research method used is quantitative, with a causal design and a survey approach. The study population consisted of students with a sample of 200 respondents who met the criteria as active e-commerce consumers. Data collection was conducted through an online questionnaire using a rating scale of 1-10. Data analysis used Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach, including measurement models and hypothesis testing through bootstrapping. The research findings show that personalized marketing affects consumer retention, consumer trust, and consumer satisfaction. Consumer trust and consumer satisfaction both affect consumer retention. Consumer trust and consumer satisfaction mediate the effect of personalized marketing on consumer retention. This study shows that personalized marketing plays an important role in increasing consumer satisfaction and trust, thereby increasing long-term customer retention. The implication of this study suggests that companies should prioritize the implementation of personalized marketing strategies supported by data analytics and CRM systems to deliver more relevant customer experiences.